Electrically Tunable Diffraction Grating Based on Liquid Crystals - Chuen-Lin Tien; Rong-Ji Lin; Shu-Hui Su; Chi-Ting Horng (Advances in Condensed Matter Physics, 2018)
A periodic electric field is generated in the grating-like electrodes cell by an applied voltage and results in the reorientation of liquid crystals. The linearly polarized probe beam experienced periodic distribution of refractive index and formed a phase grating. He-Ne laser was used as the probe beam to detect the zeroth-order (o) and first-order (+1) diffraction intensities. The experimental results showed that the diffraction grating can be switched on by applying a small voltage. The optimal first-order diffraction efficiency is about 12%. The dependence of the first-order diffraction efficiency on the polarization of the probed beam is also discussed herein.